Role of Intervenous Paracetamol as Preemptive Analgesic for Laparoscopic Cholecystectomy - Abdullah Babar, Ambareen Sifatullah, Imran Ul Haq, Muhammad Javed Khan, Khayyam Farid, Rabia Islam (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to evaluate the comparative effectiveness of preemptive paracetamol against placebo for laparoscopic cholecystectomy. Methods: After the approval from Institute review board, this randomized control trial was conducted at Department of Anesthesia, KTH, Peshawar, from 1st August 2020 to 31st January 2021. A total of 60 patients of both gender undergoing laparoscopic cholecystectomy were included in the study. Patients of Group A (n=30) received I.V Paracetamol 10mg/kg (100ml) and Group B (n=30) received 100 ml of Normal saline 10 min before skin incision. Efficacy was noted as per operational definition and noted. Results: Mean age of patients in group A and B was 34.200±5.56 and 35.900±6.28 years. Mean duration of complain in group A and B was 11.333±3.53 and 10.366±2.51 months. Mean duration of procedure in group A and B was 70.533±10.95 and 72.666±10.58 minutes. Females were predominant in the present study, with 66.7% females in group A while 60% in Group B. 22 of the patients in Group A (73.30%) had success, whereas only 10 of the patients in Group B (33.30%) did so (P= 0.002). Practical implication: this study will help to demonstrate either paracetamol can be used as analgesic in laparoscopic cholecystectomy Conclusion: In conclusion, our research shown that paracetamol had an analgesic impact on cholecystectomy patients shortly after surgery. Keywords: Laparoscopic cholecystectomy, Paracetamol, Placebo, Efficacy